Review: Peran pakan pada kejadian kembung rumen - Yanuartono - Yanuartono; Sodarmanto Indarjulianto; Alfarisa Nururrozi; Hary Purnamaningsih; Slamet Raharjo (Faculty of Animal Science, Universitas Brawijaya, 2018)
Bloat is a form of indigestion characterized by excessive gas accumulation in the rumen. Bloat occurs when the eructation mechanism is disturbed and the rate of gas production exceeds the animal's ability to expelled it. Bloat can occur very quickly due to excessive volume of gas produced in the rumen. Bloat can be classified into a primary bloat (frothy / wet bloat) mixed with rumen and secondary bloat / free bloat (free gas / dry bloat) contents in a separate free gas. There is no single method of preventing bloat events that can be applied in every different situation, however, there are methods of management in prevention and treatment that can help minimize risks. In Indonesia, although the incidence of bloat is quite high, but no data is well documented. This paper aims to review the bloat and problems in terms of understanding the clinical symptoms and the results of laboratory examination, prevention and treatment so that it is expected to be implemented by peers and field officers to reduce the risk of loss of farmers due to possible livestock death.